Shaping indigenous identity. The power of music - Udaya, Eman (UiT Norges arktiske universitet, 2017)
This thesis deals with music and expression of indigenous identity. The focus of the study is the musical performances and stories of primarily Sámi, the indigenous people inhabiting the areas of Northern Fennoscandia comprising of Norway, Finland, Sweden and the Russian Kola Peninsula. It also includes the Tuvan, the inhabitant of the Republic of Tuva in Central Asia which is a member of Russian Federation. The study situates the primary fieldwork setting Riddu Riđđu Festival, which is an important coastal Sámi and international indigenous festival, as a symbolic site where musical performances take place and indigenous identities are embodied, managed and celebrated. Taking two vocal traditions: Joik (Sápmi) and Xöömei (the Republic of Tuva) and their use in contemporary Sápmi and Tuvan soundscape, this study explores the contemplative process of understanding oneself in the process of asserting and expressing one’s indigenous identity, and the significance of music in this process. Through music, these musicians tell the tales of their lives: their experiences, encounters, attachments, belongings, emotions, and sentiments. Through music, they portray the interconnectedness to their cosmology and spirituality. Their music makes one think, rethink and question the understanding regarding indigenous identity. This thesis discusses how musical practices and performances become a process for these individuals through with they experience themselves, and also express their indigenous identity. Therefore, this thesis documents the phenomenon where music becomes a journey that leads these individual to the manifestation of their indigenous identities.